EDUKASI ISI PIRINGKU BERBASIS TEKNOLOGI DI NAGARI PADANG GANTIANG KABUPATEN SOLOK SELATAN - Vani, Ade Teti; Irwan Triansyah; Nadia Purnama Dewi; Debie Anggraini; Yuri Haiga; Aryaldy Zulkarnaini; Yanti Fitri Yasa (Nusantara Hasana Journal, 2025)
Nutritional problems remain a major challenge in community health development, particularly in rural areas. The Indonesian government has introduced the “Isi Piringku” concept as a visual guideline for balanced nutrition; however, its implementation requires more innovative educational approaches. This community service activity aimed to improve knowledge and awareness of balanced nutrition through technology-based “Isi Piringku” education as an effort to prevent nutritional problems in Nagari Padang Gantiang. The community service program was conducted in Nagari Padang Gantiang, Sangir Jujuan District, South Solok Regency, over a 21-day period. Participants included housewives, posyandu cadres, elementary school teachers, and village officials. Educational methods involved technology-based counseling using educational videos, interactive discussions, and question-and-answer sessions. The program resulted in improved participants’ understanding of the “Isi Piringku” concept, particularly the application of the 3J principles (timing, quantity, and type of food) in complementary feeding practices. Educational videos effectively facilitated comprehension of balanced nutrition messages. In addition, the activity fostered community commitment to developing a nutrition-aware village program through the establishment of a healthy garden to support complementary feeding practices. Technology-based “Isi Piringku” education is effective in enhancing community nutrition knowledge and awareness. The integration of digital media and participatory community activities can support stunting prevention efforts and promote the development of a healthy and nutrition-conscious village